Croatia on the move: Heritage, challenges, limitations - Zelimir Pasalic (European Regional Science Association (ERSA), 1998)
The efficency of infrastructure systems of countries in transition more often depends on economic rather than on technical and technological limitations. Development and functioning of the modern infrastructure systems in these countries is often coliding wit distorsions in the infrastructure markets i.e. with economic and non-economic effects of infrastructure. The national interests in integration, development and revival of some of Croatian regions, and its complete integration into European region require a systematic infrastructure strategy and policy which usually cannot be easily and quickly accomplished. It is clearly a challenge both for the present generation and the generations to come. The fundamental issues marked within the framework will be elaborated in the paper for the Congress - ERSA98.
Keywords: 330